2019
DOI: 10.1111/add.14839
|View full text |Cite
|
Sign up to set email alerts
|

Contextual characteristics of adults’ drinking occasions and their association with levels of alcohol consumption and acute alcohol‐related harm: a mapping review

Abstract: Background and AimsThere is a growing literature using event-level methods to estimate associations between contextual characteristics of drinking occasions, consumption levels and acute harms. This literature spans many research traditions and has not been brought together as a whole. This mapping review aimed to identify and describe the theoretical approaches to conceptualizing drinking occasions, study designs, predictors and outcome measures used in existing research with a view to identifying dominant ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The findings of our review are constrained by limitations of the existing literature. Our recent mapping review highlighted that papers often lack clearly stated reasons for the contextual characteristics studied, and that few studies comprehensively capture occasion characteristics . As drinking occasions have not been clearly conceptualised, there may be important contextual characteristics for understanding the situational drivers of alcohol‐related harm missing from the existing literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of our review are constrained by limitations of the existing literature. Our recent mapping review highlighted that papers often lack clearly stated reasons for the contextual characteristics studied, and that few studies comprehensively capture occasion characteristics . As drinking occasions have not been clearly conceptualised, there may be important contextual characteristics for understanding the situational drivers of alcohol‐related harm missing from the existing literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The mapping review included papers with either consumption or acute alcohol‐related harm outcomes, while the present study synthesises only papers reporting harm outcomes. The search strategy used for the mapping review is reported in detail elsewhere . Briefly, we used systematic searches of Ovid MEDLINE, Ovid PsycInfo and the Web of Science Social Science Citation Index.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations